20.1k views
2 votes
Need help how do I do this, start it, and the steps please

Need help how do I do this, start it, and the steps please-example-1
User Saca
by
6.4k points

1 Answer

3 votes
Let's solve this problem step-by-step.

STEP-BY-STEP SOLUTION:

Let's first write down the equation we are going to solve.

( 1 / 3 )h - 4 [ ( 2 / 3 )h - 3 ] = ( 2 / 3 )h - 6

To begin with, we will expand the brackets => [ ]

( 1 / 3 )h - ( 8 / 3 )h + 12 = ( 2 / 3 )h - 6

Next we will collect like terms by placing all the individual numbers on the right-side of the equation and the terms with ( h ) on the left-hand side of the equation so that we can begin making ( h ) the subject.

( 1 / 3 )h - ( 8 / 3 )h - ( 2 / 3 )h = - 6 - 12

Then we will simplify both the left-hand side and right-hand side of the equation to solve it for ( h ).

( - 9 / 3 )h = - 18

- 3h = - 18

h = - 18 / - 3

h = 18 / 3

h = 6

FINAL ANSWER:

Therefore, the answer is:

h = 6

Hope this helps! :)
Have a lovely day! <3
User Ilya Volodin
by
6.7k points